IMPLEMENTASI KEBIJAKAN ALOKASI DESA DI KECAMATAN MANANGGU KABUPATEN BOALEMO - Ramla Inaku; Juriko Abdussamad; Fenti Prihatini Dance Tui (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
This study aimed to analyze and describe the implementation of the Village Fund Allocation (ADD) policy in Mananggu Sub-district, Boalemo Regency, focusing on communication, resources, disposition/attitudes of implementers, and bureaucratic structure. The study employed a descriptive approach with qualitative analysis. Data collection techniques included observation, interview, and documentation. The findings indicate that implementing the ADD policy in Mananggu Sub-district faces significant human resources and facilities challenges. A lack of skilled personnel and limited infrastructure has resulted in inefficiencies in administration and reporting. Additionally, poor communication in task distribution and coordination among policy implementers hinders transparency and effectiveness. Although socialization efforts have been made, not all community members receive the information effectively, reducing the program's impact. While there is strong support for the policy, delays in fund disbursement remain a critical challenge. In conclusion, the implementation of the ADD policy in Mananggu Sub-district, Boalemo Regency, has not been fully optimized.